Case Report: Kampo Medicine for Non-tuberculous Mycobacterium Pulmonary Disease - Suzuki, Tomoko; Uneda, Kazushi; Aoyagi, Ryutaro; Kobayashi, Takehito; Mitsuma, Tadamichi; Nakamoto, Hidetomo (Frontiers in Nutrition, 2021)
Background: While the number of pulmonary tuberculosis cases has decreased, increase in non-tuberculous mycobacterium pulmonary disease (NTM-PD) is a global problem. Guideline-based therapy for NTM-PD sometimes causes complications that prevent treatment completion, and there are many cases of relapse even if the treatment can be completed. In addition to antibacterial treatment, care of host risk factors, such as aging, lean physique and immunosuppressive state, is also very important for the management of NTM-PD. In Japan, Kampo medicine, a traditional Japanese herbal formulation, used alone or in combination with standard multidrug therapy for NTM-PD, has been found to be effective for such cases. Case presentation: A 77-year-old lean woman had been diagnosed with Mycobacterium intracellulare pulmonary infection 6 years earlier, and had received the standard multidrug treatment 5 years later at a former hospital due to worsening of her symptoms of cough, breathlessness and hemoptysis. However, the treatment was discontinued within a year due to the development of adverse events. She refused the guideline-based antibacterial treatment, and asked for Kampo medicine instead. Bukuryoshigyakuto was subsequently prescribed, which led to cough and sputum, especially hemosputum, being well controlled. With 3 years of Kampo medicine treatment, she gained weight and her hemosputum disappeared. High-resolution computed tomography images showed improvement in her lung condition, and her sputum smear culture was negative for acid-fast bacillus. Conclusion: Various kinds of Kampo medicines have been used empirically for NTM-PD in Japan. A literature review from 1992 to 2020 showed that hozais, in particular, seem to be key drugs for the treatment of host NTM-PD risk factors. Kampo medicines can contribute to comprehensive treatment for NTM-PD management that does not rely solely on antibacterial drugs.